Strategi Digital Marketing dan Kualitas Konten Media Sosial terhadap Minat Pendaftaran Mahasiswa - Irawan, Endra; Komalawati, Euis (Universitas Prof. Dr. Moestopo (Beragama), 2025)
The rapid evolution of digital technology has significantly reshaped the communication patterns of higher education institutions. Universities are now required to adopt interactive and content-driven digital strategies to attract prospective students who are increasingly reliant on social media for decision-making. This study examines the influence of digital marketing strategy and social media content quality on student enrollment interest at Institut STIAMI. Using a quantitative approach, questionnaires were distributed to 95 newly enrolled students in the 2023/2024 academic year, selected through purposive sampling. Data were analyzed using multiple linear regression with SPSS 26.0. The results indicate that social media content quality has a positive and significant effect on student enrollment interest, while the digital marketing strategy demonstrates a positive but statistically insignificant effect. Simultaneously, both variables exert a significant influence, with a determination coefficient (R²) of 38.3%. The findings underscore the importance of authentic, relevant, and interactive content as the central factor of engagement in higher education marketing. This research contributes theoretically to the development of digital communication models in the educational sector and suggests future studies to explore engagement rate, influencer-based strategies, and AI-driven personalization in university marketing.